Keris as Branding Destination Tourism: Indonesian Heritage Daggers from Madura - Yuliana Rakhmawati; Netty Dyah Kurniasari; Ridho Marrotin Subastian (Universitas Muhammadiyah Yogyakarta, 2022)
Sumenep keris is known for its various philosophies and styles. This traditional Indonesian dagger had the potential to be developed as Madura’s brand tourism. Therefore, strategy is needed to formulate a suitable development model of Sumenep keris potential. Hence, this research aims to describe Sumenep keris potential and contribution to Madura tourism development. A phenomenological approach is used to explore the local keris artisan perspective in interpreting keris philosophy and the accompanying meaning. Data were collected through in-depth interviews and observation and the triangulation method in this research. The analysis results found that the Sumenep keris can be part of the development of a tourist destination brand. The brand will be closer to sticking to the identity of the Sumenep area as a cultural heritage tourism destination. The concept of brand development can be done by optimizing the various perspectives of the Sumenep keris as an index of Madurese culture. Since brand building for tourism destinations is a continuous process, this research is expected to be preliminary. Hence, future research can examine other forms of Madura’s culture that contribute to heritage branding tourism.